TEKANAN STRUKTURAL, PELUANG POLITIK, DAN SUKSES GERAKAN PETANI DI LAMPUNG - Hartoyo, Hartoyo (Jurnal AGRISEP, 2011)
This study was aimed at explaining  one of the conflicts in Lampung Province who developed into a peasant movement.  Interestingly, this peasant movement overran the land and agrarian policy influence to form a new village. Data were obtained from depth interviews and documentary studies. The results found that the structural pressures led to the accumulation of land conflicts crystallize into "sub-culture of peasant opposition." Its social and cultural capital were a base to accelerate the strengthening of peasants' resource mobilization. The momentum of the political opportunities at the beginning of reform responded quickly to the socio-political movements in the form of protests, negotiations and land occupation. Through this movement, the farmers has managed to occupy agricultural land, the agrarian policy changes that benefit farmers and obtained the legality of the formation of a new village Karang Rejo. However, behind this success, the substantive isues of peasants to land ownership was still neglected, so that the struggle of peasants were still not finished.